Causes of Thrombus in the Leg and Surgical Methods for its Prevention (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Lower limb thrombosis represents a major vascular disorder associated with high morbidity and risk of life-threatening complications such as pulmonary embolism. The development of thrombus in the leg results from complex interactions between vascular wall injury, blood flow disturbance, and hypercoagulability. This article analyzes the primary etiological factors responsible for lower extremity thrombosis and evaluates modern surgical approaches used to prevent thrombus formation and progression. Emphasis is placed on early risk identification, timely surgical intervention, and prevention of long-term vascular complications that lead to chronic venous insufficiency and disability. Lower extremity thrombus formation is a complex pathological condition arising from dynamic interactions between coagulation abnormalities, venous flow disturbances, and structural changes of the vascular wall. This process leads to partial or complete obstruction of venous circulation and creates a significant risk for fatal embolic events. Surgical prevention techniques have become increasingly important in modern clinical practice due to the growing number of high-risk patients and the limitations of pharmacological prophylaxis alone. This article provides an expanded analysis of the underlying mechanisms of thrombus development in the leg and evaluates the clinical effectiveness of operative approaches aimed at preventing thrombus propagation and life-threatening complications, with special attention to long-term functional recovery and reduction of disability.